ANALISIS EFEKTIVITAS PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP BELANJA PEMERINTAH KABUPATEN MUSI BANYUASIN - Rizal Efendi (Fakultas Ekonomi Universitas Tridinanti Palembang, 2012)
This study aims to analyze the effect of local revenue (PAD) of the local government expenditures Musi Banyuasin, analyzing the effect of the balance of funds to local government expenditures Musi Banyuasin and determine the level of independence that had been reached by the district Musi Banyuasin Ã‚Â The results at the district Musi Banyuasin in the period 2007-2010 shows that the revenue (PAD), and Fund Balance has effectiveness against government expenditures Musi Banyuasin. But the effectiveness of Revenue does not have any significant influence on regional spending Musi Banyuasin, while the effectiveness of the Balanced Fund has a very significant effect on their spending. In addition, the increasing trend toward shopping areas PAD indicates the level of independence of the local government district Musi Banyuasin progress though the level is still quite low. Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Keywords: Effectiveness, Revenue, Fund Balance.Ã‚Â